Palladium sub-nanoparticle decorated 'bamboo' multi-walled carbon nanotubes exhibit electrochemical metastability: Voltammetric sensing in otherwise inaccessible pH ranges - Ji, X; Banks, C; Holloway, A; Jurkschat, K; Thorogood, C; Wildgoose, G; Compton, R (2006)
A generic approach for the detection of electroactive species in potential ranges that would normally be inhibited due to the stripping of the electrocatalytic material is presented. We demonstrate, via the example of the electrochemical oxidation of hydrazine, that palladium nanoparticle (< 1 nm) decorated bamboo multi-walled carbon nanotubes exhibit a metastability such that they allow the sensing of hydrazine in the pH range where palladium metal would normally be voltammetrically stripped (oxidized) from the surface of convectional electrodes. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.